The Urgency of the Value of Islamic Education at the Stage of Parenting Program Planning in Building Parenting Collaboration in Schools and Families - Widiantari, Dian (Eduprof : Islamic Education Journal, 2025)
The increasing complexity of early childhood care requires the establishment of systematic collaboration between schools and families through the mechanism of planned parenting programs. In the context of Islamic education, the internalization of fundamental values such as rahmah, uswah hasanah, Ta'awun, and collective responsibility for child development becomes an ethical and pedagogical foundation that must be operationalized at every stage of program planning. This study aims to analyze the significance of the values of Islamic education in the planning stages of parenting programs to strengthen the collaboration of school and family parenting. The research was conducted in Pelangi toddler Daycare, West Java, Indonesia with qualitative case study approach. Data collection was conducted through in-depth interviews, participatory observations, and documentation studies involving teachers, managers, and parents. The findings of the study indicate that the integration of Islamic educational values in the planning stage contributes significantly to the alignment of parenting visions, increased communication effectiveness, and strengthening parental participation in the parenting process. Conversely, such non-value-based planning tends to result in weak coordination and low program effectiveness. This study confirms that the planning of parenting programs that are oriented to the values of Islamic education is an essential prerequisite for building effective, sustainable, and harmonious parenting collaboration between schools and families